Computation of bearing capacity in a multi-layered soil unit: A case study from Dharan, Eastern Nepal - Bhattarai, Tara Nidhi (Journal of Nepal Geological Society, 2004)
In this paper, a process of input data preparation for bearing capacity analysis in a multi-layered soil unit is presented. The method first takes into account of the engineering geological conditions of the construction site followed by geotechnical investigations that includes, among others, drilling boreholes at particulars sites also performing standard penetration test (SPT). Besides, various laboratory tests, including consolidation test, were also performed on soil samples collected from different soil layers. Finally, the soil is generalized into certain layer system and the bearing capacity of the foundation soil is computed using both shear failure as well as settlement criteria.